2009
DOI: 10.1002/pdi.1339
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm for the introduction of rapid‐acting insulin analogues in patients with type 2 diabetes on basal insulin therapy

Abstract: More than 4% of men and 3% of women in the UK are known to have type 2 diabetes. Furthermore, an ageing population and increasing prevalence of obesity, both associated with the onset of diabetes, mean that the number of people with the condition is expected to rise dramatically. Uncontrolled diabetes can lead to the development of complications such as retinopathy, neuropathy and myocardial infarction, the treatment of which places an ever increasing burden on health care services. The incidence of such compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
0
15
0
2
Order By: Relevance
“…Owens et al. proposed more stringent criteria, stating that bolus insulin should be initiated in patients who do not reach an HbA 1C < 7.0% in spite of lifestyle modifications, OAD therapy, and optimized basal insulin, which is defined as a fasting blood glucose < 5.6 mmol/L and/or a dose of > 0.7 units/kg (37). Insulin replacement is one of many treatment options that can help to bring about near normoglycemia in the patient with T2DM.…”
Section: Intensifying Insulin Therapy In Patients With Using a Basal-mentioning
confidence: 99%
“…Owens et al. proposed more stringent criteria, stating that bolus insulin should be initiated in patients who do not reach an HbA 1C < 7.0% in spite of lifestyle modifications, OAD therapy, and optimized basal insulin, which is defined as a fasting blood glucose < 5.6 mmol/L and/or a dose of > 0.7 units/kg (37). Insulin replacement is one of many treatment options that can help to bring about near normoglycemia in the patient with T2DM.…”
Section: Intensifying Insulin Therapy In Patients With Using a Basal-mentioning
confidence: 99%
“…Существуют различные подходы к проведению интен-сификации инсулинотерапии у пациентов с СД2: (1) добав-ление к терапии базальным инсулином одной инъекции аналога инсулина ультракороткого действия (инсулина лизпро, аспарт или глулизин) перед максимальным прие-мом пищи или перед завтраком (схема базал плюс) [21]; (2) последовательное добавление к терапии базальным инсу-лином 2 и более инъекций прандиального инсулина пе-ред основными приемами пищи (базис-болюсный режим терапии) [22] или (3) назначение готовых смесей инсулина с разным соотношением базального и прандиального ком-понентов (готовая смесь инсулина лизпро 75/25 (Хумалог Микс 25), готовая смесь инсулина лизпро 50/50 (Хумалог Микс 50), готовая смесь инсулина аспарт 70/30) обычно в режиме двукратного введения перед завтраком и ужином или 3 раза в день перед завтраком, обедом и ужином [23].…”
Section: стратегии интенсификации инсулинотерапииunclassified
“…Режим «базал плюс» (базальный инсулин плюс одна инъ-екция прандиального инсулина) применяется для после-довательной интенсификации инсулинотерапии у пациен-тов с СД2, которые не достигают оптимального контроля гликемии на терапии базальным инсулином, что позволяет улучшить гликемический контроль без назначения полно-го (интенсивного) режима базис-болюсной терапии [21]. Для тех пациентов, которым не удается достичь целей гли-кемического контроля на режиме базал плюс, может по-требоваться назначение дополнительных инъекций пран-диального инсулина (базис-болюсный режим терапии).…”
Section: режим базал плюс и базис-болюсная терапияunclassified
“…25 As explained below, this represents an effective strategy for a ''soft'' transition to the more physiologic (and effective) replacement of insulin by means of classical basal-bolus therapy. 24 When to move from basal to basal plus Patients eligible to start basal plus therapy are those treated with basal therapy with or without OAs who do not reach A 1C goals (<7.0% for most patients), even after adequate titration of BI to target (100-110 mg/dL [5.5-6.1 mmol/L]).…”
Section: ''Basal Plus'' Therapymentioning
confidence: 99%
“…24 When to move from basal to basal plus Patients eligible to start basal plus therapy are those treated with basal therapy with or without OAs who do not reach A 1C goals (<7.0% for most patients), even after adequate titration of BI to target (100-110 mg/dL [5.5-6.1 mmol/L]). 25 In addition, it has been suggested that also patients using high doses of BI without success (>0.7 U./kg) or who had limitations on increasing BI doses because of high risk of nocturnal hypoglycemia are good candidates. 26 Although evidence is scarce, other patients may potentially profit of basal plus therapy, as suggested by a recent experts' document, summarized in Table 1.…”
Section: ''Basal Plus'' Therapymentioning
confidence: 99%